PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN OTOMOTIF YANG TERCATAT DI BURSA EFEK INDONESIA) - Muhammad Khakani Harusi; Muhammad Ali; Muhammad Sobarsyah (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
Intense competition in the business world encourages each company to improve its performance so that the company's goals can be achieved. Companies that have gone public will always try to increase the value of the company, through capital structure, growth and profitability. This study aims to determine and analyze: the influence of capital structure and company growth on profitability. Effect of capital structure and company growth on firm value. The effect of profitability on firm value, the effect of capital structure on firm value is mediated by profitability, and to find out and analyze the effect of company growth on firm value mediated by profitability. This study uses a quantitative approach. While data collection techniques using observation, and documentation. The data analysis technique used is descriptive analysis, classic assumption test, path analysis. The results of the analysis in this study indicate that the capital structure (DER) has a negative and significant effect on profitability. Company growth has a positive and significant effect on profitability (ROA). Capital structure has a negative effect on firm value. Company growth has a significant influence in increasing the value of the company. High profitability (ROA) will have an influence in increasing the value of the company. Mediation test results show that profitability can mediate the effect of capital structure (DER) on firm value. It can be seen that the capital structure (DER) affects profitability (ROA) so that it has implications for the low value of the company (PER). Mediation test results show that profitability can have an effect on firm growth on firm value, which means that corporate growth affects the increase in profitability (ROA) which has implications for increasing company value (DER).